An update on the spider genus Hexophthalma (Araneae: Sicariidae) in the Afrotropical region, with descriptions of new species - Lotz, Leon (European Journal of Taxonomy, 2018)
The described Afrotropical species of the genus Hexophthalma Karsch, 1879 (under the genus name Sicarius Walckenaer, 1847), of the spider family Sicariidae Keyserling, 1880, were recently reviewed. In the present paper the Afrotropical species of the genus Hexophthalma are revisited. After a thorough examination of all the available specimens from nine major collections, the species H. testacea (Purcell, 1908) is here synonymized with H. hahni (Karsch, 1878), three new species are described – H. binfordae sp. nov., H. goanikontesensis sp. nov. (both from Namibia) and H. leroyi sp. nov. (from South Africa) – and the male of H. dolichocephala (Lawrence, 1928) is described for the first time. The distribution of the species is also revised and a new updated key to the species is compiled.